Mekanisme Kompleks Sepsis dan Syok Septik - Purwanto, Diana S.; Astrawinata, Dalima A.W. (Jurnal Biomedik : JBM, 2018)
Abstract: Sepsis and septic shock are still important medical problems. As sepsis progresses to septic shock, the risk of death increases significantly. Sepsis is a complex mechanism which can include infectious pathogen with its virulence factors, host response, inflammatory response, impaired coagulation system, and organ dysfunction. The complexity of the pathogenesis and pathophysiology of sepsis involves almost all types of cells, tissues, and organ systems.Keywords: sepsis, septic shockAbstrak: Sepsis dan syok septik masih merupakan masalah medis yang penting. Seiring penjalanan sepsis menjadi syok septik, risiko kematian meningkat secara signifikan. Sepsis ialah mekanisme kompleks yang dapat meliputi patogen penyebab infeksi dengan faktor virulensinya, respon pejamu, respon inflamasi, sistem koagulasi yang terganggu, dan disfungsi organ. Kompleksnya patogenesis dan patofisiologi sepsis melibatkan hampir semua jenis sel, jaringan, dan sistem organ.Kata kunci: sepsis, syok septik